ELECTRONIC CONTROL SYSTEM OF THE AIR TRANSPORT ENTERPRISES - Salii, T. M. (Science and Transport Progress, 2007)
Advantages of appendix of modern informations technologies are sure on the whole and electronic turn of documents in particular, as facilities of increase of efficiency of activity air enterprises.